Предмет: Математика, автор: heysss

5.25 ,5.26, 5.29, 5.31

Приложения:

Ответы

Автор ответа: NNNLLL54
0
lim_{xto 0}, frac{5-3^{x+2}}{3+2^{x+3}}=frac{5-3^2}{3+2^3}=frac{-4}{11}\\lim_{xto 2}frac{x^2-6x+8}{x^2+x+12}=lim_{xto 2}frac{(x-2)(x-4)}{x^2+x+12}=frac{0}{2^2+2+12}=0\\lim_{xto 3}frac{x^2-2x+6}{x+3}=frac{3^2-6+6}{3+3}=frac{9}{6}=frac{3}{2}\\lim_{xto a-1}frac{x^2+x+a}{x+1}=frac{a^2-2a+1+a-1+a}{a-1+1}=frac{a^2}{a}=a
Автор ответа: GreedySquirrel
0
Как-то так..
[здесь есть 20 символов]
Приложения:
Похожие вопросы